2020
DOI: 10.1109/jphot.2020.2979938
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Beam Self-Cleaning in Tapered Yb-Doped GRIN Multimode Fiber With Decelerating Nonlinearity

Abstract: We experimentally demonstrate spatial beam self-cleaning in an Yb-doped gradedindex multimode fiber taper, both in passive and active configurations. The input laser beam at 1064 nm was injected for propagation from the small to the large core side of the taper, with laser diode pumping in a counterdirectional configuration. The Kerr effect permits to obtain high-beam quality amplification with no accompanying frequency conversions. As a result, our nonlinear taper amplifier may provide an important building b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The corresponding experimental setup is described and presented in Ref. 11 At first, we characterised our tapered amplifier by studying the amplified spontaneous emission (ASE) noise, and the amplification of the 1064 nm signal as a function of the pump LD power. Fig.…”
Section: Small-to-large (S-l) Core Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding experimental setup is described and presented in Ref. 11 At first, we characterised our tapered amplifier by studying the amplified spontaneous emission (ASE) noise, and the amplification of the 1064 nm signal as a function of the pump LD power. Fig.…”
Section: Small-to-large (S-l) Core Configurationmentioning
confidence: 99%
“…5 Subsequent experiments have shown that the output transverse spatial distribution at high powers may be controlled, by varying the fiber coupling conditions of the input laser. 8 Nonlinear pulse propagation and beam reshaping in standard or tapered GRIN MMFs [9][10][11] have been investigated in both the normal and in the anomalous dispersion regime, 12,13 using pulses with duration ranging from sub-nanoseconds to femtoseconds. [14][15][16] Active MMFs are key components for a future generation of fiber lasers, which may enable to scale-up by orders of magnitude the peak power of mode-locked laser sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the available gain in fiber lasers, provided by active rare-earth doping [1,2], is limited by the presence of Raman and Brillouin scattering, and transverse mode instabilities (TMI) [3,4]. Using a tapered Yb-doped (YD) MMFs, with a varying fiber core size along its axis, is a solution to mitigate TMI, hence to obtain high output quality beams by filtering high-order modes [5].…”
mentioning
confidence: 99%
“…In this work, we experimentally demonstrate spatial KBSC in a tapered YD MMF, where the laser pulse propagates from the smallest to the widest core. The experimental setup is described [5]. Briefly, the injected laser pulses at 1064 nm, propagating from the small (47 µm) to the large (96 µm) diameter of a 5 m tapered YD GRIN MMF.…”
mentioning
confidence: 99%